Determination of Flavonoid Concentration, Phenolic Concentration, and Antioxidant Activity of Allium cepa L Extract - Alfita Dhurrotul Lu'ma; Mirwa Adiprahara Anggarani (IKIP Mataram, 2022)
Free radicals are unstable molecules caused by several electrons in the molecule that does not have a partner. Free radicals can potentially trigger the onset of various degenerative diseases. One of the efforts that can be made to ward off the disease is by consuming antioxidant compounds. Antioxidant compounds can be found in plants with the genus Allium, such as Allium cepa L. This study aims to determine antioxidant activity, flavonoid concentration, and phenolic concentration in Allium cepa L extract. The DPPH method (2-2-diphenyl-1-picryhydrazil) is used to determine antioxidant activity, calorimetrically determined flavonoid consensuality with AlCl3, and the Follin-ciocalteu method is used to determine the phenolic consensual consensuality in the sample. The multilevel maceration method in sample extraction uses different polarity solvents, dichloromethane, ethyl acetate, and 96% ethanol. Based on the research data, flavonoid and phenolic compounds were found in 96% ethanol extract but in dichloromethane and ethyl acetate extracts were not found. The concentration of flavonoid ethanol extract is 96% by 4,125 mgQE/gr extract. Phenolic concentration in ethanol extract was 96% by 1,071 mgGAE/gr extract. The IC50 value in ethanol extract is 96% which is 201,221 ppm. These results show that the antioxidant activity of Allium cepa L is classified as moderate, with IC50 values being between the range of 100-250 ppm.